Anchored transponder guided lung radiation therapy - Dobelbower, Michael; Herth, Felix; Gompelmann, Daniela; Röder, Falk (Practical Radiation Oncology, 2020)
Purpose - The Calypso Beacon transponder has been modified by the addition of a nitinol anchor feature to allow for positional stability when implanted bronchoscopically into the lung. The purpose of this study was to confirm the feasibility and safety of anchored transponder placement and feasibility of lung target localization and tracking. - Methods and Materials - This study enrolled patients with histologically confirmed cancer in the lung (primary or metastatic) who were scheduled to receive external beam radiation therapy. Three anchored transponders were implanted via flexible bronchoscopy into small (approximately 2- to 2.5-mm diameter) airways. Patient alignment at each radiation fraction was performed with the Calypso system, and anchored transponder position was tracked during radiation delivery. The primary endpoint was defined as the ability to localize at least 85% of the patients during the first week of treatment. Four follow-up visits were specified including a posttreatment assessment and every 3 months up to 1 year. - Results - A total of 69 patients underwent anchored transponder placement, and all 207 implanted anchored transponders were visible on the treatment-planning simulation computed tomography scan. Sixty-seven patients underwent radiation therapy, and localization was successful in 66 cases (98.5%). With 1 failure in 67 cases, the P value for rejecting the null hypothesis was <.001 and the primary objective of the study met. Five adverse events in 5 patients were potentially attributed to the study device or implantation procedure, consisting of pneumonia (2 cases), pleural abscess (1 case), and pneumothorax (2 cases). Two serious events (cardiac arrest and acute hypotension) were attributed to anesthesia during the implantation procedure. - Conclusions - This study strongly supports that anchored transponders are safe, positionally stable, and useful for lung tumor localization and monitoring.
Available online 31 August 2019
Gesehen am 20.02.2020